JURIDICAL REVIEW ARRANGEMENT OF COMPLETE SYSTEMIC LAND REGISTRATION (PTSL) IN LAND CERTIFICATION CASE STUDY IN THE LAND OFFICE OF WATES VILLAGE - Siti Sri Wahyuni; Darmawan Tri Budi Utomo; Mieke Anggraeni Dewi (Jurnal Meta-Yuridis, 2023)
The aim of this research is to find out the implementation of a complete systematic land registration arrangement at the Grobogan District Land Office and to find out the supporting and inhibiting factors that arise in the complete systematic land registration activity at the Wates Land Office. The method used in this study is a normative juridical research method through a direct survey in Wates supported by secondary data. The method for analyzing data is a qualitative method. Research results show the implementation of complete systematic land registration (PTSL) arrangements in 2022 at the Wates Land Office. the implementation of PTSL is carried out with the following stages and implementation of activities: a. planning; b. preparation; c. location determination; d. Establishment and determination of the adjudication committee and task force; e. Extension; f. certificate issuance process; g. research on juridical data to prove rights; h. Announcement of physical data and juridical data and their ratification; i. Affirmation of conversion, recognition of rights, and grant of rights; j. bookkeeping and issuance of certificates of land rights; k. submission of the certificate of land rights; l. Reporting; m. Digitization. Supporting factors; a. Participatory maps which are very supportive in planning activities for implementing juridical measurements and implementation; b. Wates Village officials who actively participate in filing PTSL activities; c. Communities who participate assist in delineating the boundaries of land parcels in measurement activities. Factors that become obstacles; a. Misunderstanding of village officials when applying for PTSL files; b. There are still many land boundary disputes between residents in Wates Village, Kedungjati District; c. The stakes or boundary markers for the land parcels that will be registered with the PTSL certificate have not been installed; d. Found land that has been certified as participating in PTSL activities; e. Revision of PBT after the announcement of physical data and juridical data; f. PTSL difference process last year and 2022